Manajemen Kurikulum Pesantren Salaf Darul Falah “Amtsilati” Jepara - Mufassirul Alam; Fikri Maulana (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2021)
This study aims to describe the curriculum at the Darul Falah Islamic Boarding School "Amtsilati" Jepara related to curriculum planning, curriculum organization, curriculum implementation, and curriculum evaluation. This research is motivated because this salaf pesantren has a unique curriculum compared to other salaf pesantren. This research uses descriptive qualitative research method. Data collection techniques in this study were through interviews, observation, and documentation studies. Data analysis went through two stages. The first stage, analysis of the preliminary study before going to the field. The second stage, data analysis in the field with data reduction, data presentation, and drawing conclusions. The results showed that the curriculum was implemented with the curriculum and syllabus formulation. The organization of the curriculum is done by determining the curriculum and the division of tasks for teachers or ustaz. The implementation of the curriculum is carried out through a learning process and assessment as well as a report on learning outcomes. Evaluation is done by studying the subjects and the time of the learning implementation.